Constitutional Complaint Dalam Rangka Penegakan Hak Asasi Manusia di Republik Indonesia - Bertho Plaituka, Solidaman (Jurnal Media Hukum, 2016)
The Constitutional Court exists to oversee the RI State Constitution contained therein and the protection of human rights enforcement. Protection of constitutional rights of citizens by the Court comes through constitutional review authority. But in the mechanism, the Court protect the constitutional rights of citizens to the extent of constitutional rights are violated by the provisions of the law, so the law will be declared contrary to the constitution. In fact, the possibility of violations of citizens’ constitutional rights not only through the normative provisions of a law. There are many way and possible that violation of the constitutional rights of citizens, either by the authorities or by the actions of other parties. In this condition we know that constitutional complaint very urgent in Constitutional Court in Indonesia.